Os degraus do recrutamento partidário: o caso da filiação na cidade do Rio de Janeiro - Guedon, Philippe Chaves (2019)
The political parties are the main objective of study of this paper. They can be observed through multiple ways as: electoral, governmental and organizational are some examples. But, the literature about political parties privileged, for a long time, the parties only as actors in the electoral dispute. Starting in the 90's, mainly, there is a turn around in the literature that initiates the observation of the parties through their own internal structures and the impacts of this, in a last analysis, upon the democratic representation. With this in mind, this paper will point out, in a detained way, the process of party recruitment using as argument that the concept should be seen in an amplified way with the affiliation as one of the initial phases. With this being said, we will dedicate our attention to the process of party affiliation through two forms. The first is analyzing the public data of the superior electoral court constructing an idea of affiliation in a local level; the second, through a survey with members of PT e DEM, exploring the profile of these members, theirs interests and their relation with the parties. To synthesize, the objective is explore the field of affiliation in political parties understanding it as the first step in the political process of formation of the political elites taking into consideration the local reality of the City Rio de Janeiro.